A cautionary note for forest landscape restoration in drylands: cattle production systems in northwest Madagascar’s dry forests - Randrianasolo, R.; Ranjatson, P.; McLain, R.; Nomenjanahary, A.R.F.; Manasoa, C.G.O. (Informa UK Limited, 2022)
Multiple global initiatives are underway to restore the world’s forests, and more recently, its rangeland ecosystems. Tenure security has been identified as a key enabling factor for successful restoration initiatives. However, in Madagascar, a global biodiversity hotspot, dry forests are considered unoccupied and unowned, even where communities have long-established claims under customary tenure systems. Collective tenure recognition efforts are underway, but limited knowledge on agropastoralist cattle production strategies hampers efforts to develop well-informed tenure reforms. Our qualitative study helps fill this knowledge gap by documenting cattle raising strategies among agropastoralists in northwestern Madagascar, as well as the core elements of semi-extensive and extensive pasturelands. Our analysis reveals the presence of four distinct cattle raising strategies in the study area but suggests that cattle raisers are transitioning away from extensive cattle production toward semi-extensive and intensive alternatives in response to high risk of cattle theft and expanding human settlement. Although our study focuses on Madagascar, the issues we raise are relevant to ongoing efforts throughout sub-Saharan Africa to engage agropastoralists in dry forest restoration and support their livelihoods.